PENGEMBANGAN E-MODUL IPS BERBASIS PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Yeyen Suryani; Iis Mediawati; Iskandar (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
improving the quality of education. Field observations indicate that many students have not yet reached the expected standards, making this a fundamental issue that needs to be addressed with appropriate learning strategies. In addition, student learning outcomes have not met the criteria for achieving learning objectives. Contributing factors include the limited availability of media and instructional materials suited to students’ characteristics, resulting in monotonous and less engaging learning that hinders active participation in the learning process. Therefore, this study aims to develop a Social Studies e-module based on differentiated learning to enhance students’ critical thinking skills. The research employed the ADDIE development design, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through questionnaires, interviews, and tests. Expert validation results indicated that the developed e-module was highly feasible. A limited trial using an independent t-test obtained a significant value of 0.001, indicating a difference in post-test results between the experimental and control classes. A broader trial using One-Way ANOVA yielded a significant value of 0.898, suggesting no significant differences between schools. The study concludes that the Social Studies e-module based on differentiated learning is valid, interactive, flexible, student-centered, and effective in improving students’ critical thinking skills. Keywords: Critical Thinking Skills, Differentiated Instruction, E-Module, IPS